Distribution of high-level mupirocin resistance among clinical MRSA. (4th July 2017) - Mahmoodzadeh Hosseini, Hamideh; kiyani, Nasibeh; Amin, Mohsen; Hedayati Ch, Mojtaba; Imani Fooladi, Abbas Ali
Abstract : Mupirocin is a topical antibiotic for methicillin-resistant Staphylococcus aureus (MRSA) decolonization in hospital settings and nursing homes and is used as a highly effective antibiotic against MRSA. In this study, we aimed to evaluate the frequency of high-level mupirocin-resistant (HLMR) strains among the MRSA subtypes. A total of 188 clinical MRSA isolates were collected from 2011 to 2014, and their susceptibility to antimicrobial agents and vancomycin resistance was evaluated using disc diffusion method and micro-dilution method, respectively. Furthermore, the presence of mecA, SSCmec, mupA and mupB was assessed by PCR. All isolates were multi-drug resistant (MDR) but 2 strains (1.06%) were resistant to mupirocin. Minimum inhibitory concentration (MIC) of vancomycin for 8 strains (4.7%) was higher than 2 μg/ml. Of 188 isolates, 188 (100%), 64 (34.04%), 8 (4.3%), 150 (79.8%), 26 (13.8%), 2 (1.06) and 2 (1.06%) isolates possessed mecA, SCCmec types I, II, III, IV, mupA and mupB genes, respectively. Our data showed that despite infection control policy enforced by health care committee, the rate of mupirocin resistance among MRSA strains is continuously rising.